Investigation on fish health and diseases in rural pond aquaculture in three districts of Bangladesh (Journal of the Bangladesh Agricultural University, 2014)
The present study was conducted to know the culture strategies and fish health and disease problems in pond aquaculture in Mymensingh, Bogra and Pabna districts of Bangladesh. Questionnaire interview and participatory rural appraisal tools like focus group discussion (FGD) were conducted with selected fish farmers. In total 90 farmers were interviewed and 9 FGD sessions were conducted. Most of the respondents practiced carp and pangas polyculture and they had disease problems in their ponds. Prevalence of fish disease varied with cultured species and locations. The most prevalent diseases as reported by the farmers were pop eye (57.78%), ventral reddening (55.55%), tail and fin rot (48.89), hemorrhagic lesion over the body surface (45.56%), dropsy (40%), gill rot (40%), white spot (40%) and epizootic ulcerative syndrome or EUS (33.33%). According to farmers opinion most susceptible species to disease was silver carp, Hypophthalmichthys molitrix (57.78%); followed by mrigal, Cirrhinus cirrhosus (50%); catla, Catla catla (47.78%); sarputi, Barbodes gonionotus (47.78%); rui, Labio rohita (42.22%) and pangas, Pangasianodon hypophthalmus (42.22%). Higher mortality was found in pangas (53.56%). Clinically, pangas, koi and sarputi were found severely affected. Most of the farmers used some treatment measures against disease problems. This study also highlited some fish health management problems in pond aquaculture. Further studies should include identification and characterization of pathogens involved in different types of diseases in pond aquaculture. DOI: http://dx.doi.org/10.3329/jbau.v11i2.19944 J. Bangladesh Agril. Univ. 11(2): 377-384, 2013